2013
DOI: 10.1259/dmfr.20120234
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency heating of metallic dental devices during 3.0 T MRI

Abstract: Objectives: To estimate the risk of injury from radiofrequency (RF) heating of metallic dental devices in use during 3.0 T MRI. Methods: The whole-body specific absorption rate (WB-SAR) was calculated on the basis of saline temperature elevation under the maximum RF irradiation for 15 min to determine the operation parameters for the heating test. The temperature changes of three types of threeunit bridges, a full-arch fixed dental prosthesis and an orthodontic appliance in use during MRI with a 3.0 T MR syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…0 T. Most previous ex vivo tests performed to assess objects for MR safety used units with a static magnetic field of 1.5 T or lower (6). MRI at 3 Tesla or higher has become common in daily practice (7)(8)(9), and some clinical MRI operate at up to 9.4T (10).…”
Section: Introductionmentioning
confidence: 99%
“…0 T. Most previous ex vivo tests performed to assess objects for MR safety used units with a static magnetic field of 1.5 T or lower (6). MRI at 3 Tesla or higher has become common in daily practice (7)(8)(9), and some clinical MRI operate at up to 9.4T (10).…”
Section: Introductionmentioning
confidence: 99%
“…In our trial, no bracket temperature increase exceeding 0.1°C has been found, which corresponds with other studies 30,31 . Contrarily, Görgülü et al 29 reported a stainless steel bracket set heating up to 3.04°, while Hasegawa et al 41 noted a temperature rise of 2.61°. Such heterogeneity was probably caused by different exposition time, significant variation of tested appliance design and dissimilar heat transfer conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, which aimed to measure RF heating during MRI, artificial teeth were used 18 or the orthodontic appliances were inserted directly into gelled phantom models. 19,20 In the present study, to simulate actual clinical conditions, 40 human teeth were used for the application of brackets and wires.…”
Section: Discussionmentioning
confidence: 99%